2018
DOI: 10.1016/j.diabres.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Time- and frequency-domain measures of heart rate variability predict cardiovascular outcome in patients with type 2 diabetes

Abstract: Time- and frequency-domain measures of HRV independently predicted cardiovascular outcome in patients with T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 41 publications
2
27
0
1
Order By: Relevance
“…Likewise, Razainskaite-Virbichiene et al (36) demonstrated that in patients with T1DM, the parameters of time domain in supine position have a coefficient of variation <1.65, reflecting a sensitivity of 94.3% and specificity of 91.5% for the diagnosis of CAN. Additionally HRV variables were independent predictors for developing cardiovascular disease (CVD) in patients with T2DM (28,30,34,36). These findings are in agreement with our results that showed improvement in rest HRV parameters in response to short interventional treatment, as opposed to dynamic tests that remained unchanged.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Likewise, Razainskaite-Virbichiene et al (36) demonstrated that in patients with T1DM, the parameters of time domain in supine position have a coefficient of variation <1.65, reflecting a sensitivity of 94.3% and specificity of 91.5% for the diagnosis of CAN. Additionally HRV variables were independent predictors for developing cardiovascular disease (CVD) in patients with T2DM (28,30,34,36). These findings are in agreement with our results that showed improvement in rest HRV parameters in response to short interventional treatment, as opposed to dynamic tests that remained unchanged.…”
Section: Discussionsupporting
confidence: 90%
“…Resting heart rate variability was advocated by some authors as a sensitive and specific method for diagnosis of cardiovascular dysautonomia. Besides that, it is easier to be performed than dynamic tests and does not need patient collaboration (28)(29)(30)(31)(32)(33)(34)(35). Takase et al (28) found that a cut-off point <30ms in SDNN parameter has a sensitivity of 72% and specificity of 92% for CAN diagnosis in patients with type 2 diabetes, while Ziegler et al (30) showed that HF index was more sensitive than functional tests to detect precocious autonomic disorder in patients with diabetes, using 0,892 as a cut-off.…”
Section: Discussionmentioning
confidence: 99%
“…A teljesítményspektrum-analízis során a szívfrekvencia-variabilitást nyugalmi helyzetben vizsgálva az alacsony frekvenciájú (0,04-0,15 Hz) és a magas frekvenciájú (0,15-0,4 Hz) komponenseket vizsgálják. Az alacsony frekvenciájú komponensek a paraszimpatikus, míg a magas frekvenciájúak a szimpatikus aktivitást jellemzik [27].…”
Section: A Szívfrekvencia-variabilitás Vizsgálataunclassified
“…HRV represents one of the most promising markers. A joint European Society of Cardiology and North American Society of Pacing and Electrophysiology task force de ned and established standards of measurement, physiological interpretation, and clinical use of HRV, and the most widely used methods can be grouped under the time domain and frequency domain methods [4,5]. Established clinical data based on numerous studies consider HRV have been proven useful in detecting CAN in diabetes patients [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Although HRV and ESC are validated and can serve as screening tools for CAN in patients with diabetes [5,[12][13][14][15][16], there is paucity of information that focuses on its role in estimating CAN severity in patients with diabetes who was already diagnosed with CAN in outpatient clinics, owing to the possible bene ts of exploring the role of the CV autonomic function on subsequent CV events and the consequent development of therapeutic strategies to reduce the prevalence of CV events.…”
Section: Introductionmentioning
confidence: 99%